Analaysis of Waste in Improving Sustainability Manufacturing for Springbed Production at CV Indohome - Suryaningsih, Fania Damayanti; Handayani, Wiwik (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
The increase in the Purchasing Managers Index of Indonesia, is driven by the high domestic demand as well as the increase in production activity. CV IndoHome is engaged in springbed manufacturing, serving customers business-to-customer. This results in product specifications that are diverse and tailored to individual requirements. So indicates the production process is potentially wasted. The objective of this research is to identify critical waste using the Waste Assessment Model method, identify the root causes of the occurrence of critical wastes with the Fishbone diagram, and produce alternative recommendations for improvement with Sustainability Manufacturing Value Analysis. The results of the research show that the waste crisis in the production process is Motion, Inventory, and Overproduction. Waste crisis that occurs due to various interrelated things and alternative improvement can be done application of sustainability principles requiring maximization of factory space and resource utilization, empowerment of employees through training, improvement of productivity, and the use of technology.